Brillouin fiber laser with a 49 cm long Bismuth-based erbium-doped fiber - Harun, Sulaiman Wadi; Shahi, Sharifeh; Ahmad, Harith (IOP Publishing, 2010)
Brillouin fiber laser (BFL) has been demonstrated using a 49 cm long bismuth-based erbium-doped fiber (Bi-EDF) in conjunction with a 20 m long photonic crystal fiber as gain media with a simple ring resonator. The BFL operates at 1559.09 nm, which is 0.09 nm shifted from the Brillouin pump wavelength. The BFL also has a stable output with a side mode suppression ratio of 12 dB.